PENGARUH PENGENDALIAN INTERNAL, KUALITAS AUDITOR, INDEPENDENSI KOMITE AUDIT, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Alvin Kautsar Pinandhito; Agung Juliarto (Diponegoro Journal of Accounting, 2016)
The objective of this research is to analyze the influence of internal control, auditor quality, audit committee independence, firm size, and leverage. Measurement of tax aggresiveness utilizes book tax difference (BTD). This research refers to research conducted by Lanis and Richardson (2013) with some modification.Population of this research were manufacturing companies that listed in Indonesian Stock Exchange (IDX) during 2011-2014. Data were collected by using purposive sampling method. A total data of 230 observations were analyzed. Multiple linear regression analysis was used as a main analysis tool. The results of this research show that only auditor quality significantly influences the level of Tax Aggresiveness. Whereas, internal control, audit committee independence, firm size, and leverage have no significant effects on the level of Tax Aggresiveness.